(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current study was conducted from the ninth month of the year 2019 to the end of the sixth month of 2020 aiming and evaluating the effectiveness of the fungus Beauveria bassiana in controlling the Periplaneta americana. More than 250 samples were collected, and the most of them were collected for the purpose of studying Biology control. The fungus Beauveria bassiana was used in the control, where the fungus was used in four different concentrations and kneaded by mixing with water and dilution, where the concentrations were used (0.25 × 107, 0.5 × 107, 0.75 × 107.1 × 107) and all recorded death rates of 100% in nymphs after the passage of (244,168,120,96) respectively, and in adults, a murder rate was recorded after (244,192,144,120) hours respectively, and there were significant differences in the percentage of homicide between adults and nymphs.